Accountability and Transparency Analysis of Village Fund Allocation Management in Villages in Pujud District, Rokan Hilir Regency - Hastuti, Irena Puspi; Yusrawati, Yusrawati; Siska, Siska (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the Accountability and Transparency of Village Fund Allocation Management in villages in Pujud District, Rokan Hilir Regency. The number of villages in this study amounted to 13 villages. This study uses a qualitative descriptive analysis technique that describes the research from the results of interviews and direct observations on the object of research. The results of this research are Village Financial Management Accountability in the Village in Pujud District, Rokan Hilir Regency at the administrative, reporting and accountability stages in accordance with Minister of Home Affairs Regulation No. 113 of 2014. However, in the transparency stage of Village Financial Management in the Village in Pujud District, Rokan Hilir Regency, it is not fully appropriate. with Permendagri No. 113 of 201, because the village has not fully provided access to information regarding cash in and cash out to the community regarding the allocation of village funds. And the access to media information has not been maximized to provide information on the APBDesa Realization and Accountability Report. Therefore, it can be concluded that the Transparency of Village Financial Management in Pujud District, Rokan Hilir Regency is not yet transparent.